Creating Healthier Salad Dressings at Home - Lori Johnson; Jill Breslawski; Marie Arick; Kendra Zamojski; Amarat Simonne (EDIS, 2021)
This publication provides an overview of salad dressings as well as tasty homemade salad dressing recipes. Written by L. Johnson, J. Breslawski, M. Arick, K. Zamojski, and A. Simonne, and published by the UF/IFAS Department of Family, Youth and Community Sciences, December 2021.